A Continental Free Trade Area in the Absence of the Free Movement of People is Inconceivable - Lehlongwa, Thulane (South African Yearbook of International Law)
The African Free Trade Continental Agreement (AfCFTA) represents renewed efforts by the current cohort of African leaders to move the continent closer to its self-reliance ambitions, and it aims to build on the foundation laid by the founding fathers of the African Union aimed at achieving a better life for Africans through deeper regional economic integration. Central to achieving the Agreement’s objectives is the realisation of the free movement of persons, which is envisaged to be a vehicle for deeper regional integration. This article provides a brief conceptual analysis of the Free Movement of Persons concept, its benefits in driving regional integration, successes, and the potential challenges that may hinder the full realisation of the AfCFTA’s objectives as a mutually reinforcing agenda. In addition to contributing to existing literature, this article explores whether the Free Movement of Persons is indeed a sine qua non for the success of the AfCFTA. Drawing on lessons from the implementation of other regional trade integration projects, the European Union integration model, in this instance, the article recommends key interventions to bolster implementation efforts.